Upaya Mengurangi Kecanduan Gadget melalui Layanan Bimbingan Klasikal pada Siswa Kelas 12 - Veby Agustina; Gebi Rissing Lallo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the effectiveness of classical guidance services in reducing gadget addiction among twelfth-grade students. Gadget addiction has become a growing concern in modern educational settings, as excessive use of digital devices often interferes with students’ academic performance, social interactions, and emotional stability. The research applies a quantitative methodology with a quasi-experimental approach, specifically utilizing a one-group pretest-posttest design. Participants were selected through purposive sampling based on indications of high gadget dependency. The intervention was conducted through structured classical guidance sessions focusing on awareness building, self-control improvement, and practical time management skills. Data were collected using a validated gadget addiction scale administered before and after the intervention, then analyzed using parametric statistics to determine the significance of the results. The findings indicate a significant decrease in gadget addiction levels following the implementation of the classical guidance program. This result highlights the importance of preventive and developmental counseling services in schools. The study implies that classical guidance can serve as an effective strategy to help students regulate their digital behavior and foster healthier lifestyle patterns in the digital era.